PENGARUH KEPEMIMPINAN AUTENTIK PADA EMOSI POSITIF, KEPERCAYAAN, DAN HARAPAN SERTA DAMPAKNYA PADA KOMITMEN ORGANISASIONAL - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study examines the effect of authentic leadership on hope, trust in leaders and positive emotions. In addition, this research also tests the influence of hope, trust in leaders and positive emotions on organizational commitment. This research conducted in survey research framework with cross-sectional data type. Total of 140 respondents completed the questionnaire with self-administered survey. The Authentic Leadership Questionnaire (ALQ), State Hope Scale, The Trust in Management Scale, Positive and Negative Affect Schedule (HEAT-Short Version), and Organizational Commitment Questionnaire were used to measure the variables involved. Hypothesis testing with SEM (Structural Equation Modeling) shows several findings. The results showed a positive and significant effect of authentic leadership with hope, trust in leaders and positive emotions. Positive influence was also shown in the trust on a leader to organizational commitment. While the positive influence of hope and positive emotions towards organizational commitment is not supported.